APOLOGY STRATEGIES USED BY AIRLINE OFFICERS IN HANDLING PROBLEMS WITH PASSENGERS - Natalia GY Maitimu; Esther H Kuntjara (Kata Kita: Journal of Language, Literature, and Teaching, 2016)
In this research, I discuss about types of apology strategies used by Lion Group officers in handling problems with passengers. It was triggered by the fact that this Airline Company still manages to have high number of passengers though many of its passengers have been disappointed because of the service given. Here, I used Apology Strategies theory proposed by Eva Ogierman (2009) which divided Apology Strategies into three main categories and each category has its own types. To get the data, I conducted an observation within two weeks in Pattimura Airport, Ambon. From this study I found out that there is a difference in the use of types of apology strategies when the officers had to deal with both calm and emotional passengers. The officers used types of IFIDs category more frequently in dealing with emotional passengers.